Upaya Guru Bimbingan dan Konseling dalam Meningkatkan Resiliensi Akademik Siswa Selama Pembelajaran Jarak Jauh - Hengki Satrianta; Anna Rufaidah; Afiatin Nisa; Sabrina Dachmiati (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2021)
Online learning as an effort to minimize the transmission of Covid-19 has a negative effect on student learning activities. Saturation, decreased motivation, and low student attention occur in the field. Academic resilience is needed so that students are able to survive and achieve the targeted academic achievements. The efforts of Guidance and Counseling (BK) teachers are needed for that. This study aims to determine how the efforts of BK teachers in improving students' academic resilience during online learning. This was a descriptive qualitative research. Data in this study were obtained through six informants namely the principal, vice principal of the curriculum field, two BK teachers, and two students. Data were collected by in-depth interviews, observations, and documentation notes. Data were analyzed through reduction, display, and verification techniques as well as conclusions. The results showed that to improve students' academic resilience during distance learning BK teachers took preventive actions through information services, curative through individual and group counseling, and promotive through the introduction of BK performance profiles.